APERIODIC Report Trainers of Teacher Trainers (TTT) Evaluation. TTT Evaluation Progress Report No. 1. - Illinois Univ., Urbana. Center for Instructional Research and Curriculum Evaluation; Illinois Univ., Urbana. Center for Instructional Research and Curriculum Evaluation ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1969)
This is the first of a series of reports to be issued at irregular intervals to communicate the plans, progress, and findings of the evaluation of the Trainers of Teacher Trainers (TTT) Program. The first 12 pages of the report outline in three general categories the activities carried out to date: 1) visits to cluster meetings and individual projects and conversations with key people connected with TTT; 2) staff meetings to bring together the results of information collected during visits; 3) the preliminarydevelopment of interview schedules, questionnaires, and observational techniques. The remainder of the report contains the data-gathering devices that have been developed: the Cluster Meeting Observation Form, the TTT Cluster Meeting and Clustering Questionnaire, the Cluster Meeting Registration Form, the Site Visitor Briefing Postal Cards, the Site Visitor Questionnaire, and the Site Visitor Briefing Session Observation Instrument. (RT)
Sponsoring Agency: Consortium of Professional Associations for the Study of Special Teacher Improvement Programs.
Sponsoring Agency: Office of Education (DHEW), Washington, DC.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Evaluation Methods; Program Evaluation; Teacher Educator Education; Training Teacher Trainers Project